Integrasi Edukasi Parenting dan Kewirausahaan melalui Program Sekolah Orang Tua Hebat (SOTH): Strategi Pemberdayaan Ibu Rumah Tangga di Desa Karangwaluh, Kabupaten Ponorogo - Smita Catur Sudyantara; Mila Diana Sari; Susantriana Dewi; Rizqi Rahmawati; Rahmad Kurniawan; Takim Mulyanto (BADAN PENERBIT STIEPARI PRESS, 2025)
Housewives play a crucial role in shaping children's character and supporting family economics. However, limited access to parenting education and entrepreneurial skills hinders their optimal contribution in both areas. This community service initiative aims to empower housewives in Karangwaluh Village, Sampung District, Ponorogo Regency through an integrated program combining parenting education and entrepreneurship training. The